In the wrong place - alien marine crustaceans distribution, biology and impacts - Galil, Bella S.; Clark, Paul F.; Carlton, James T. (Invading Nature - Springer Series in Invasion Ecology, 2011)
In The Wrong Place: Alien Marine Crustaceans - Distribution, Biology And Impacts provides a unique view into the remarkable story of how shrimps, crabs, and lobsters ? and their many relatives? have been distributed around the world by human activity, and the profound implications of this global reorganization of biodiversity for marine conservation biology. Many crustaceans form the base of marine food chains, and are often prominent predators and competitors acting as ecological engineers in marine ecosystems. Commencing in the 1800s global commerce began to move hundreds ? perhaps thousands ? of species of marine crustaceans across oceans and between continents, both intentionally and unintentionally. This book tells the story of these invasions from Arctic waters to tropical shores, highlighting not only the importance and impact of all prominent crustacean invasions in the world's oceans, but also the commercial exploitation of invasive crabs and shrimps. Topics explored for the first time in one volume include the historical roots of man's impact on crustacean biogeography, the global dispersal of crabs, barnacle invasions, insights into the potential scale of tropical invasions, the history of the world's most widely cultured shrimp, the invasive history and management of red king crabs in Norway, Chinese mitten crabs in England, and American blue crabs in Europe, the evolutionary ecology of green crabs, and many other subjects as well, touching upon all ocean shores.